Isolation and Identification of Flavonoids from Arctiumlappa Stem and Study the Hepatoprotective Effecton Acetaminophen Induced Liver Damage - Zaid Abd Al Salam Alsamarrai1 , Abdulsalam Tawfeeq Alsamaraiand2 , Rafah Razooq Al-Samarrai3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The present study investigate the hepatoprotective and antioxidant effect of crude extract of Arctiumlappastem(E-ALS) and isolated total flavonoids(ITF) from the stem, With qualitative and quantitative determination of flavonoids by HPLC.Twenty four local adult male rabbitswere used in this study which divided into four groups(6animal in each group), Control-1(C1) as control group, Control-2(C2):treated with 300mg/kgparacetamoladministrated for one week, Group 1(G1): 300mg/kg paracetamol administrated for one week +Orally 250mg/kg of E-ALSadministrated daily for 4 weeks, Group 2(G2): Orally 300mg/kg paracetamol administrated for one week +Orally 50mg/kg of ITFdministrated daily for 4 weeks. The results identified five types of flavonoids for the first time in plant stem (Rutin, Myricetin, Quercetin, Apigenin, Kaempferol) with quantified determination for the concentration of each type of flavonoids in E-ALS and also in ITF which identified the same five flavonoids. The hepatoprotective effect of E-ALS and ITF were observed by monitoring the antioxidant parameters and activity of liver enzymes. The results obtained from this study showed that the levels of glutathione-GSH, Glutathione peroxidase GPX and Glutathione-S-Transferase-GST were significantly (P ? 0.05) decreased in C2 treated with paracetamol as comparing with C1, with significant (P ? 0.05) elevation of alanine aminotransferase-ALT activity and non-significant effect on Aspartate aminotransferase-AST, while the level of GSH and GPX were significantly (P ? 0.05) elevated in G1 and G2 treated with E-ALS and ITF respectively as compared with C2, in which the levels of GSH and GPX are less than the levels in C1 and G1. Otherwise the levels of GST, ALT and AST significantly (P ? 0.05) decreased in G1 and G2 as compared with C2. These findings show the hepatoprotective properties of E-ALS and IFT against liver injury induced by paracetmol and also the protective role of anti-oxidative defense system of flavonoids in the two extracts.